IMPROVING THE STUDENTS’ READING COMPREHENSION THROUGH SCAFFOLDING READING - Fiqhi Yulianingsih; Bahrun Amin; Radiah Hamid (English Language Teaching Methodology, 2021)
This pre-experimental research aimed at finding out whether or not the use of Scaffolding Strategy are able to improve the students’ literal and critical reading comprehension at the Eleventh Grade Students of SMA Negeri 19 Gowa. The population of this research were the Eleventh Grade Students of SMA Negeri 19 Gowa in academic year 2019/2020. The researcher used a Purposive Sampling and took class XI IPA 1 as the sample of the research which consisted of24 students. The research used reading comprehension test as instrument. The result of this research found that the use of Scaffolding Reading could improve the students’ reading comprehension in term of literal and in term of critical reading comprehension. It based on the research result, the score of the students reading comprehension including the students’ literal reading improved (19.17%) from the mean score in the test in pre-test is 69.16 to be 88.33 in post-test. Besides, the students’ critical reading skill improved (17.5%) from the total score in pre-test is 69.33 to be 85.83 in post-test. It indicates that the score of the students’ reading comprehension in term of literal and critical reading in each indicator in post-test were greater than the pre-test.